2023
DOI: 10.1007/s12144-023-04641-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cultural intelligence on burnout among practitioners working with migrants: an examination of age, gender, training, and language proficiency

Abstract: Migrants are a vulnerable population that often requires specialized care and support. Practitioners who work with migrants must be knowledgeable about the unique challenges they face. Some first-line practitioners are better equipped to work in intercultural environments because they possess higher cultural intelligence (CQ). This study aims to examine the impact of cultural intelligence on burnout among practitioners working in 15 countries. It also compares levels of CQ in relation to age, gender, education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
1
0
0
Order By: Relevance
“…These findings partially support Hypothesis 2, highlighting the nuanced roles different aspects of Cultural Intelligence play in this context. Our findings are aligned with other studies that showed the impact of Cultural Intelligence beyond the educative context on workers’ burnout when interacting with immigrants, highlighting the relevance of cultural competence in professional success ( Puzzo et al, 2023 ).…”
Section: Discussionsupporting
confidence: 91%
“…These findings partially support Hypothesis 2, highlighting the nuanced roles different aspects of Cultural Intelligence play in this context. Our findings are aligned with other studies that showed the impact of Cultural Intelligence beyond the educative context on workers’ burnout when interacting with immigrants, highlighting the relevance of cultural competence in professional success ( Puzzo et al, 2023 ).…”
Section: Discussionsupporting
confidence: 91%